U.S. Veteran Population Projections, 2015 through 2040: Implications for Health Planning and Monitoring Population Health Outcomes - Gregory Fant (Public Health, 2019)
IntroductionA population’s structure and how it may change over time could affect the interpretation and use of health service utilization rates. This informative report describes how data for Veteran population composition age group and sex could have important implications for the comparison of rates as health planners consider the long-term resources necessary to support rehabilitation, health and wellness, and Veteran reintegration.MethodsU.S. Veteran population projections were examined. Secondary data were used to examine the population structure of Veteran and U.S. adult populations from 2015 to 2040. Population pyramids were constructed.ResultsThe projected Veteran population for 2040 is lower than that in 2015. During the same period, the U.S. adult population is projected to increase. Close inspection of the population pyramids for 2015 to 2040 showed that between these years, not only would the proportion of female Veterans increase over time but, also, there will be more Veterans in the older age groups. ConclusionsAs Veterans Health Administration (VHA) modernizes health system operations, health outcomes and health service utilization rates over time will be an important component for monitoring progress and refining health planning activities. The report, also, proposes a “standard reference population” for the comparison Veteran population rates from 2018 to 2030.